The Application of Growth Mindset Training-based Classical Guidance to Improve Psychological Well-Being of High School Students - Purwaningsih, Lia; Isti‘adah, Feida Noorlaila; Sugara, Gian Sugiana (Quanta : Jurnal Kajian Bimbingan dan Konseling dalam Pendidikan, 2025)
This study aims to determine the effectiveness of growth mindset training in improving psychological well-being. The research utilized a quasi-experimental approach with a Non-Equivalent Control Group Design involving experimental and control groups. The sample consisted of students with low levels of psychological well-being. The analysis results indicated that the independent t-test showed a significance value (Sig(2-tailed)) of 0.000, which is statistically significant, indicating the effectiveness of the intervention. A difference was found in the psychological well-being post-test scores between the control group (M=86.82, SD=9.71) and the experimental group (M=97.47, SD=8.89). Additionally, an improvement was observed in the experimental group's scores from the pre-test (M=85, SD=11) to the post-test (M=97.5, SD=9). The study concluded that growth mindset training effectively enhances students' psychological well-being. This training encourages students to believe in change, fosters perseverance and resilience in facing challenges or problems, and serves as a factor in discovering life's meaning. The study contributes to the scientific literature on the effectiveness of growth mindset training in improving students' psychological well-being. It provides empirical evidence that a growth mindset can be a strategic approach to supporting student's mental and emotional development.